A EDUCAÇÃO DO CAMPO SOB AS PERSPECTIVAS SOCIOLÓGICAS DE PIERRE BOURDIEU NO CONTEXTO DAS ESTRUTURAS SOCIAIS - Pereira de Souza Silva, Gessiedna (LINKSCIENCEPLACE, 2026)
This work aims to understand the theoretical and practical approaches of the Field Education and sociological studies of Pierre Bourdieu in the perspective of social class structures. Since field education starts from social struggles against the hegemony of urban spaces, by the rights of the subjective visibility of the peasant space, based on the assumption that there are no differences in legal rights between urban and rural spaces. Some works by Pierre Bourdieu rightly denote the questions of social class as the habitus; cultural capital; the symbolic power; those excluded from the interior; the heirs and the reproduction to which the peasants are identified in the same situations. The Education of the Field, like Pierre Bourdieu, who was born of a society that was dominated and suffered great symbolic violence, overcame the social oppressions it received, so much so that peasant subjects with opportunities of institutionalized state and habitus incorporated or objectified emancipate and live without worry with the symbolic violence of those who think they are dominating. For the subjects of both the countryside and the urban are citizens who need to get out of the comfort zone and seek their best against the social structures that rank social classes inferiorly.